Perkembangan Pasar Uang dan Pasar Modal di Malaysia: Studi Perbandingan dengan Indonesia - Yasri Azwar Siregar; Maryam Batubara (Economic Reviews Journal, 2026)
This article examines the development of the money market and stock market in Malaysia and compares it with conditions in Indonesia. The study employs a descriptive-qualitative method based on a literature review of academic publications, official reports from financial authorities, and stock exchange statistics from both countries published within the last five years. The findings indicate that Malaysia's capital market, regulated by Bank Negara Malaysia and the Securities Commission Malaysia, has grown relatively steadily, with Bursa Malaysia's market capitalisation reaching approximately RM2.05 trillion in the third quarter of 2024 and the highest number of listed companies in the ASEAN region. Malaysia also maintains its position as a global Islamic finance hub, with sukuk serving as a core instrument of its money and capital markets. Meanwhile, the Indonesia Stock Exchange recorded a larger nominal market capitalisation, yet its market-capitalisation-to-GDP ratio remains relatively lower than Malaysia's. Indonesia's money market is being strengthened through Bank Indonesia's regulatory reforms and its money and foreign exchange market deepening roadmap toward 2030. Studies on ASEAN capital market integration show a relatively strong short-term linkage between the Indonesian and Malaysian capital markets. The article concludes that both countries share a broadly aligned direction of financial market development, while differing in the pace of market deepening, investor literacy, and the role of Islamic finance.